2019
DOI: 10.1007/s13592-018-0631-x
|View full text |Cite
|
Sign up to set email alerts
|

Sound recordings of Apis cerana japonica colonies over 24 h reveal unique daily hissing patterns

Abstract: The simultaneous wing movement by multiple worker bees in a colony produces a hissing sound, which is a novel acoustic and vibrational signal of the honey bees. Hissing of honey bees is thought to be a response to direct, threatening stimuli. However, we discovered Japanese honey bees (Apis cerana japonica ) can hiss even without obvious disturbances in previous study. In this study, to understand the temporal characteristics of honey bee hissing, we conducted 24-h sound recordings over 7 months in 2015 and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Hisses were part of how colonies responded to hornet attacks in our study, but colonies also hissed under no-attack conditions. This latter finding agrees with previous studies showing that A. cerana colonies hiss without apparent provocation [80,136]. Because of their timing in this study, it is unlikely that hisses are used to deter high-threat hornet predators.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hisses were part of how colonies responded to hornet attacks in our study, but colonies also hissed under no-attack conditions. This latter finding agrees with previous studies showing that A. cerana colonies hiss without apparent provocation [80,136]. Because of their timing in this study, it is unlikely that hisses are used to deter high-threat hornet predators.…”
Section: Discussionsupporting
confidence: 93%
“…Discrete signal features help to avoid ambiguity, aligning with predictions of greater communicative complexity when species are highly social and have sophisticated predator defences [9,129,130]. While hisses are considered aposematic warning signals in many animal taxa, including bees [32,48,80,127,131135], the role hisses play in A. cerana defence is not clear [77,80,136]. Hisses were part of how colonies responded to hornet attacks in our study, but colonies also hissed under no-attack conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Sound analysis was used to monitor the learning process of worker bees (Apis mellifera), where they responded to an electric shock with a hissing response characterized by loud sounds and vibrations [38]. Further research explored the relationship between hissing onset/offset times and sunrise/sunset, indicating that honeybees hiss predominantly during daylight hours, with the highest frequency at dawn [39]. Therefore, different conditions or states in a hive result in bees producing different sound signals, which can provide useful information for beekeepers if interpreted appropriately.…”
Section: Resultsmentioning
confidence: 99%
“…Lasso logistic regression and singular value decomposition are currently available to analyse the sound of hives to identify sound patterns in queenless bee colonies (Robles-Guerrero et al, 2019). Kawakita et al (2019) recorded hive sounds of Apis cerana japonica over 24 h, and they found that Apis cerana japonica hissing had unique temporal patterns. Cejrowski et al (2020) also presented a method that uses Mel Frequency Cepstral Coe cients (MFCCs) features and an SVM classi er to de ne the start and the end of the presumed bees-night in summer.…”
Section: Introductionmentioning
confidence: 99%